The manager's pocket guide to emotional intelligence : from management to leadership - Sterrett, Emily A. (Managers Pocket Guide Series., 2000)
One of the keys to becoming a true leader is emotional intelligence. Emotional intelligence quotient (or EQ) encompasses qualities that go beyond general intellectual intelligence and technical competency. EQ includes self-awareness, self-control, self-confidence, motivation, empathy, and competencies in the social environment. These hallmarks of a true leader can be learned. The activities in this guide will help strengthen the reader's EQ skills, resulting in a more successful career and a more satisfying life.